Oblikoslovno-skladenjske posebnosti rezijanščine - Benacchio, Rosanna (Slavistična revija, 1998)
The article deals with some morpho-syntactic pecularities of Resian dialect (among other things, with the expression of definiteness, some pecularities of pronominal clitic forms, modal meaning of the imperfect) and points out the parallels in other Slavic languages as well as in Friulian and Italian.
Keywords: oblikoslovje; rezijanščina; skladnja; slovenska narečja; slovenščina